'Making Friends with the Beast?' Reflections on the Women, Peace and Security Agenda - Robin May Schott (The Royal Danish Library, 2013)
UN Res. 1325 is a revolutionarytransformation of rhetoricregarding issues of women, peace,and security. In the last dozen years,there has been a proliferation ofdebates about its successes and itsfailures. Should its limitations beunderstood as failures in implementation?Or should the concepts ofwomen, gender, and violence whichframe the resolution be criticallychallenged?